2005
DOI: 10.1007/s10620-005-2463-6
|View full text |Cite
|
Sign up to set email alerts
|

Butyrate-Induced Differentiation of Colon Cancer Cells Is PKC and JNK Dependent

Abstract: Butyric acid, a short-chain fatty acid physiologically present in human large gut, is derived from bacterial fermentation of complex carbohydrates. It has been shown to reduce the growth and motility of colon cancer cell lines and to induce cell differentiation and apoptosis. Apoptosis is considered a result of normal colonocyte terminal differentiation in vivo. The aim of this study was to characterize the cellular mechanisms regulating differentiation of colon cancer cells stimulated with sodium butyrate (Na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
61
1
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(75 citation statements)
references
References 52 publications
10
61
1
3
Order By: Relevance
“…Overexpression of PKCßII in colonic epithelium seems to results in hyperproliferation and an increased susceptibility to carcinogenesis with an early increase in carcinogenesis, whereas PKC was downregulated in colonic tumors (43,44). Data from Orchel et al (45) have shown that differentiation of Caco-2 cells by butyrate treatment is dependent on PKC and c-Jun N-terminal kinase (JNK) activity. In LIM1215 and CaCo-2 colon carcinoma cells, butyrate reduced total protein kinase C (PKC) activity and specifically reduced the expression of PKC· and PKCε subtypes, an effect that was reproduced by incubations with a specific inhibitor of histone deacetylase (46).…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of PKCßII in colonic epithelium seems to results in hyperproliferation and an increased susceptibility to carcinogenesis with an early increase in carcinogenesis, whereas PKC was downregulated in colonic tumors (43,44). Data from Orchel et al (45) have shown that differentiation of Caco-2 cells by butyrate treatment is dependent on PKC and c-Jun N-terminal kinase (JNK) activity. In LIM1215 and CaCo-2 colon carcinoma cells, butyrate reduced total protein kinase C (PKC) activity and specifically reduced the expression of PKC· and PKCε subtypes, an effect that was reproduced by incubations with a specific inhibitor of histone deacetylase (46).…”
Section: Discussionmentioning
confidence: 99%
“…2). Multiple intracellular kinases in the oncogenic or survival signaling pathways have been illustrated to be key players in butyrate actions (27,28). Western blotting using monoclonal antibody against the C terminus of AKAP12 showed decreased expression of the full-length protein and an appearance of a truncated isoform at a molecular mass…”
Section: Cluster A: Growth Arrestmentioning
confidence: 99%
“…3 In vitro, sodium butyrate (NaB) is a potent differentiating agent for several colorectal cancer cell lines (CRCs). [4][5][6] NaB-mediated cell cycle withdrawal of CRCs appears to be dependent on acetylation of histones and consequent changes in transcription, requiring continuous protein synthesis and the expression of p21. 7 It has recently been shown that 1 mM NaB is the best working concentration to activate the differentiation program in CRCs without triggering apoptosis, whereas 5 mM NaB is sufficient to induce a p53-independent apoptotic cell death by activating a pathway involving p38, PPARg and caspases.…”
mentioning
confidence: 99%
“…7 It has recently been shown that 1 mM NaB is the best working concentration to activate the differentiation program in CRCs without triggering apoptosis, whereas 5 mM NaB is sufficient to induce a p53-independent apoptotic cell death by activating a pathway involving p38, PPARg and caspases. 6,8 Several intracellular signaling cascades have been implicated in the regulation of the proliferation-differentiation balance in enterocytes by the coordinated expression of the genome in response to environmental cues. During enterocyte differentiation of CRCs the ERK pathway is switched off, whereas PI 3 K class I and p38 activities are increased and essential for full differentiation.…”
mentioning
confidence: 99%